Financing of basic education in Mercosul: A comparative analysis of the sources, volume, and nature of resources (2000-2015) - Diniz Júnior, Carlos Antônio; Santos, Thauan (Education Policy Analysis Archives, 2022)
This article analyzes the mo(ve)ments of education financing in the Southern Common Market (Mercosul), composed of Argentina, Brazil, Paraguay, and Uruguay, based on the sources, the volume and the nature of the resources destined to the area, covering the period from 2000 to 2015. Based on a quali-quantitative approach, this research presents a hybrid methodology. After a brief review of the literature on the relevance of education in Mercosul, we carry out a documentary analysis of the normative orders associated with the financing of education in the four countries under analysis, aiming to highlight the sources of these resources. Then, there is a quantitative analysis of the evolution of government spending on basic education (total and percentage participation in GDP and public expenditure), the nature of expenditure (current or capital), enrollments (total and profile, if public or private institution) and spending per student (total). To this end, we use data from the Economic Commission for Latin America and the Caribbean (ECLAC), the UNESCO Institute for Statistics (UIS) and the World Bank. Among the main results, the expansion of spending accompanied the expansion of coverage of school attendance and that the increase in the share of public expenditure in GDP was not followed by the increase in annual expenditure per student.